Strategic planning of the school principals in downtown Riyadh and its relation to the level of administrative excellence - Al-Khlewi, Leena Sulaiman; Al-Arefe, Asma Sulaiman; Al-Harbi, Nawal Naif (Journal of Educational and Psychological Sciences, 2019)
This study aimed to identify the role of strategic planning in the achievement of administrative excellence. To achieve this objective, the study researchers used the descriptive survey method where the questionnaire has used as a tool for the study. The sample of the study was randomly selected nd. Consisted from 41 female leaders of public elementary schools in Central Riyadh. The result of the study showed that the level of administrative excellence was significant. The study also showed that there is a direct correlation statistically significant at level (0.01) between strategic planning and administrative excellence in Riyadh’s elementary schools. Moreover, there are no statistically significant differences between the mean responses of family members on strategic planning (in different variables: job and years of experiences) and administrative excellence in public elementary school. The researchers recommended the establishment of workshops and training courses in the field of strategic planning for school leaders in order to increase the efficiency of applying the strategic planning, the awareness of it and its effective contribution in achieving strategic planning in schools. Finally, it plays a noticeable role in practicing both general planning and strategic planning in particular.